Gamifikasi Evaluasi Pembelajaran: Pengaruh Durasi Waktu Media Wayground terhadap Fokus dan Ketetapan Jawaban Siswa pada Pelajaran Pendidikan Agama Islam - Tiara Kusuma Wardani; Gilang Maulana Jamaludin; Encu Mulya Syamsul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Conventional assessment frequently triggers cognitive anxiety that undermines students' focus, causing evaluation results to inadequately reflect their true abilities. This study aims to examine the effect of answer time duration variations on students' focus and response accuracy in Wayground-based digital evaluation in Islamic Religious Education (PAI). A quantitative approach with repeated measures design was employed, involving 21 students of Grade IV at SDN Liangjulang 6. Evaluations were conducted in three sessions with varying time durations per question 30 seconds, 20 seconds, and 10 seconds, using the paper mode feature of the Wayground platform. Prior to evaluation session, students participated in a simulation session to ensure readiness and uniform understanding of the mechanism. Data were analyzed using the Shapiro-Wilk normality test, Friedman test, and post hoc Wilcoxon test with Bonferroni correction. The results indicate a significant difference in students' response accuracy across time duration conditions, with the 20-second duration yielding the best and most consistent performance compared to other durations. This study concludes that the 20-second duration represents the optimal time allocation in gamification-based digital evaluation for enhancing students' focus and response accuracy in PAI learning at the elementary school level.